ENIGMA OF SOCIAL HARM - Raymen, Thomas, author. ([S.l.])
1 online resource
Keywords: Drawing on a novel blend of moral philosophy, social science, psychoanalytic theory and continental philosophy, this book offers up a diagnosis of contemporary liberal capitalist society and the increasingly febrile culture we occupy when it comes to matters of harm. On what basis can we say that something is harmful? How are we supposedto judge between competing opinions on the harmfulness of a particular behaviour, practice, or industry? Can we avoid drifting off into relativism when it comes to judgements about harm? In an age of deep cultural and political discord about what is and is not harmful, providing answers to such questions is more important than ever. Appraising the current state of the concept of social harm in academic scholarship and every-day life, Thomas Raymen finds a concept in an underdeveloped state of disorder, trapped in interminable deadlocks and shrill disagreements about what should and should not be considered harmful. To explain the genesis of this conceptual crisis and identify what we need to do to resolve it, The Enigma of Social Harm travels from Graeco-Roman antiquity to the present day, exploring trends and developments in moral and political philosophy, religion, law, political economy, and culture. Along the way, we see how such trends and developments have not only made it more difficult to establish a shared basis for evaluating harm, but that the tools which might enable us to do so are now outright prohibited by the political-economic, cultural, and ethical ideology of liberalism that dominates contemporary society. Written in a clear and accessible style, it is essential reading for all those interested in matters of social harm, justice, politics, and ethics.